Clinicopathological study of diabetic foot in Bundelkhand area with special reference to fungal infection in asymptomatic feet of diabetic patients - Mishra, Mayank; Pratap, Dinesh (International Surgery Journal, 2017)
Background: As with substantial increasing in incidence of diabetes mellitus in present century and with huge prevalence in population; the incidence of one of the dreadful complication of diabetes i.e. diabetic foot also increases, leading to increase morbidity and mortality. Fungal infection in foot is one of the underweighted cause of foot ulceration. These microulceration in conjunction with diabetes may leads to fulminant infection. The study comprised of 66 cases out of which 16 served as control. Aim and objectives of our study is to study the incidence of fungal infection in asymptomatic feet of diabetic patients, identification of the type of fungus, comparison with nondiabetics and clinicopathological study of the patients. Methods: The present study was carried at Department of Surgery, MLB. Medical College, Jhansi, the study group was classified into two groups. Control group; this group comprised of non-diabetic patients with foot lesions. Disease group; diabetic patients with foot lesions. Webs scrapings were inoculated in Sabouraud’s media slopes. Cultured media were examined after 3 days for the growth. Identification depends on colonial appearance and the morphology of the spores and by Gram, s and AFB Staining. Results: By this study we conclude that fungal infection in asymptomatic foot of diabetes patient are significantly more than non-diabetic patients which is accentuated by duration, type, glycaemic control and practice of bare foot walking which makes diabetic patient more prone for diabetic foot. So, the foot care of patients of diabetes should include the prophylactic steps to prevent fungal growth. Conclusions: By above study, we reasonably conclude that fungal infection in diabetic patients plays a pivotal role in formation of diabetic foot disease, so by eradication of fungal infection in asymptomatic foot of diabetic patient by general preventive methods and/or pharmacological methods may be beneficial in reducing morbidity and mortality in diabetic foot patients.